PENGARUH PELAYANAN PUBLIC RELATION, SISTEM DISTRIBUSI TERHADAP KEPUASAN PELANGGAN PADA PT ADHYA TIRTA BATAM - Emilna Tesra Putri,; Yossi Hendriati, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This research was conducted with the aim of knowing the effect of public relations services, distribution systems on customer satisfaction at PT Adhya Tirta Batam. The independent variables in this study are public relations and distribution systems. The dependent variable in this study is customer satisfaction. This study uses a purposive sampling method by distributing 80 sets of questionnaires to ATB customers in the city of Batam who have a bill of 100 million and above according to the bill every month. The questionnaire contained 16 questions, each of which represented a related variable and also the researcher conducted data processing using SPSS version 25. The results of this study are public relations significantly influence customer satisfaction. The distribution system has a significant effect on customer satisfaction. public relations and distribution systems significantly influence customer satisfaction by 72,9%